The Future of Islamic Banking in the Philippines: Finding a Niche - De Castro, Kenneth Michael A. (Animo Repository, 2022)
Among the United Nations’ Sustainable Development Goals are economic growth and reducing inequality. Sustainable economic growth can drive progress, create decent jobs for, and improve living standards, whereas reducing inequality ensures that no one is left behind in all aspects of human life. Bridging sustainable economic growth and reduction of social inequality is financial inclusion. As individuals and businesses have access to useful and affordable financial products and services that meet their needs, it helps them manage their current consumption, invest for the future, and mitigate their exposure to various financial and economic risks. In the case of the Philippines, achieving financial inclusion for all is still a long way to go. According to the 2019 Financial Inclusion Survey by the Bangko Sentral ng Pilipinas, 71% of the total Filipino adult population remains unbanked and have their financial needs underserved. These people have limited access to formal sources of capital to support their financial and economic goals. More specifically, the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), one of the 17 administrative regions in the country, remains to be the least financially-inclusive region and the most impoverished, with a poverty incidence rate of 37% (National Economic and Development Authority, 2021). Hence, in an effort to strengthen its mandate of sustainable financial inclusion, especially in the most impoverished areas such as BARMM, former President Rodrigo Roa Duterte signed Republic Act No. 11439 which seeks to usher the creation of Islamic banks and Islamic banking units within conventional banks to introduce an alternative financial system compliant with Shariah or the Islamic law. With this legislation, Islamic banking can augment country’s existing financial system by providing additional readily-accessible, cheaper, and sustainable financing for Muslim Filipinos and for all Filipinos, as a whole.